Relationship between Corporate Governance Index and Firm Performance: Indian Evidence. Issue 3 (June 2018) - Arora, Akshita; Bodhanwala, Shernaz
The Indian corporate governance norms have been evolving over a period of time but limited number of studies have been undertaken with reference to corporate governance index (CGI) in the Indian context. The study aims to examine the relationship between CGI and firm performance. We construct CGI using important parameters of governance such as board structure, ownership structure, market for corporate control and market competition. Our panel data set comprises of listed firms and the estimation analysis has been carried out using random effects method. The study reveals significant positive relationship between CGI and firm performance metrics. CGI is an important and causal factor in explaining firm performance. The investors would also have positive perception about business firms maintaining high governance standards, thus reducing possible funding costs.